Posidonia Oceanica and Wood chips activated carbon as interesting materials for hydrogen storage. (18th May 2020) - Pedicini, Rolando; Maisano, Susanna; Chiodo, Vitaliano; Conte, Giuseppe; Policicchio, Alfonso; Agostino, Raffaele G.
Abstract: The goal is to investigate the feasibility to use a local biomass (Posidonia Oceanica and Wood chips), as a raw precursor, to the production of activated carbons (AC) with a high surface area and remarkable hydrogen (H2 ) adsorption properties. Biomasses (particle size of 0.3–0.4 mm) were pyrolyzed at 600 °C with a heating rate of 5 °C/min under an argon atmosphere. The biochar obtained from the carbonization step was chemically activated with KOH. The activation methodology induces a considerable improvement of the properties of the porous carbon in terms of carbon content (from 58 to 69 wt% to 93–96 wt%), surface area (from 41 to 425 m 2 /g to 2810–2835 m 2 /g) and H2 adsorption in cryogenic condition (from 0, 1 wt% to over 5 wt%). All porous carbons were characterized in terms of elemental analysis (CHNS–O), textural properties and H2 adsorption measurements. Graphical abstract: Image 1 Highlights: High Surface Activated Carbon for hydrogen physisorption. Fully reversible hydrogen storage. Simple, cheap and effective synthesis process. Suitable for static and automotive application.